A Review of Omics Studies on Arboviruses: Alphavirus, Orthobunyavirus and Phlebovirus - Peinado, Rafaela dos S. [UNESP]; Eberle, Raphael J.; Arni, Raghuvir K. [UNESP]; Coronado, Mônika A. (MDPI, 2022)
Since the intricate and complex steps in pathogenesis and host-viral interactions of arthropod-borne viruses or arboviruses are not completely understood, the multi-omics approaches, which encompass proteomics, transcriptomics, genomics and metabolomics network analysis, are of great importance. We have reviewed the omics studies on mosquito-borne viruses of the Togaviridae, Peribuyaviridae and Phenuiviridae families, specifically for Chikungunya, Mayaro, Oropouche and Rift Valley Fever viruses. Omics studies can potentially provide a new perspective on the pathophysiology of arboviruses, contributing to a better comprehension of these diseases and their effects and, hence, provide novel insights for the development of new antiviral drugs or therapies.
Keywords: arboviruses; genomics; metabolomics; omics; proteomics; transcriptomics